Геохронометрія докембрійських зон діафторезу в кристалічних породах північно-західної частини Українського щита - Павлова, О.О.; Пономаренко, О.М. (Мінералогічний журнал, 2010)
Розглянуто можливості використання K-Ar геохронометрії для датування процесів діафторезу у докембрійських рухомих зонах на прикладі північно-західної частини Українського щита. Комплекс петрографічних, міне ралогічних та хронометричних досліджень асоціації калійвмісних мінералів із порід зон тектонічних порушень дозволяє правильно інтерпретувати ізотопні дати їх походження та здійснювати хронометраж метаморфічних і тектонічних подій у докембрії. Рассмотрены возможности использования K-Ar геохронометрии для датирования процессов диафтореза в докембрийских подвижных зонах на примере северо-западной части Украинского щита. Комплекс петрографических, минералогических и хронометрических исследований ассоциации калийсодержащих минералов из пород зон тектонических нарушений позволяет правильно интерпретировать изотопные даты их происхождения и осуществлять хронометраж метаморфических и тектонических событий в докембрии. The example of using K-Ar geochronometry for dating the processes of diaphthoresis in Precambrian mobile zones of north-western part of the Ukrainian Shield (USh) is considered. K-containing minerals formed in the course of diaphthoritic transformations of initially magmatic rocks have been chosen to determine the beginning and termination of the process of diaphthoresis. These minerals also fix radiogenic argon at different temperatures, covering a range of 690—250 °C. Such minerals are widespread in Paleoproterozoic crystalline rocks and are represented by hornblende and biotite. Technically reworked and diaphthorised granitoids of Korninsk granite massif and orthoamphibolites found in a junction zone between Volynsk and Ros'-Tikich megablocks of USh, as well as diaphthorically altered magmatic rocks of Osnytsya block were taken as reference objects of investigation. It was established, that K-Ar dating being carried out in combination with petrographic, microstructural and structural-genetic investigations, it is possible to find the age of separate stages of tectonic transformation of certain metamorphic rocks, zones of tectonic dislocations and even whole regions. For example, the age of formation of Kornin granite on zircons is defined as 2068 Ma; the age of crystallization of zircon coatings regenerated during diaphthoresis and formation of hornblende is estimated, accordingly, as 1980—2020 and 1975 Ma; the age of thermofixing of biotite syngenetic with amphibole in the bulk tectonised granite is established as 1790 Ma; and in cleavage notchings the age of 1735 Ma is determined. The same evolutionary trends are fixed in some other investigated objects of diaphthoresis. In investigations at the regional scale, practically all the territory of north-western part of USh escape conditions of such mode of metamorphism at the age boundary of 1650—1550 Ma. More prolonged thermoactivity in the form of peculiar "hot points" remained active in such areas as within the boundaries of Osnytsya block around the settlements Klesov—Vera, in southern board and in the central part of the Sushchany-Perga zone, southwards of Buky massif, along the Central fault within Korosten pluton, on separate sites of Ros'-Tikich megablock and around Litinya dome of Dniester-Bug megablock. The complex of additional petrographic and mineralogical investigations of associated potassium-containing minerals from diaphthorised rocks, allows one to make correct interpretation of isotopic dating concerning their origin and to carry out age chronometric timing of metamorphic and tectonic events which took place in Precambrian.